Through the Fractured Looking Glass. Issue 5 (December 2020) - Mitchell, Sandra D.
Abstract : I argue that diversity and pluralism are valuable not just for science but for philosophy of science. Given the partiality and perspectivism of representation, pluralism preserving integration can increase accuracy. Perspectivism is often supported by appeal to visual representation. I draw further insights from multimodel sensory integration for understanding experiment-based predictions of protein structure. The epistemic lessons learned from the scientific case also apply to philosophy of science itself. Finally, I suggest that a critical, nuanced philosophical view of legitimate sources of pluralism in science has an important role to play in public discourse.